2005
DOI: 10.1002/cne.20854
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic and neuronal localization of the scaffold protein Na+/H+ exchanger regulatory factor 2 (NHERF‐2) in mouse brain

Abstract: The Na + /H + exchanger regulatory factor 2 (NHERF-2) is a scaffold protein that regulates cellular signaling by forming protein complexes. Several proteins known to interact with NHERF-2 are abundantly expressed in the central nervous system, but little is known about NHERF-2 localization in the brain. By using immunohistochemistry combined with light and electron microscopy, we found that many populations of astrocytes, as well as some populations of neurons, were immunopositive for NHERF-2 throughout the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
(43 reference statements)
3
12
0
Order By: Relevance
“…Our observation that NHERF2 was present in endothelial cells of blood vessels and capillaries throughout the brain is consistent with recent data published in mouse brain using the same antibody (Paquet et al, 2006). In addition, however, the study in mouse brain showed labeling for NHERF2 in other cell types, including astrocytes and neurons.…”
Section: Distribution Of Nherf1 and Nherf2 Proteins In The Rat Brainsupporting
confidence: 92%
See 2 more Smart Citations
“…Our observation that NHERF2 was present in endothelial cells of blood vessels and capillaries throughout the brain is consistent with recent data published in mouse brain using the same antibody (Paquet et al, 2006). In addition, however, the study in mouse brain showed labeling for NHERF2 in other cell types, including astrocytes and neurons.…”
Section: Distribution Of Nherf1 and Nherf2 Proteins In The Rat Brainsupporting
confidence: 92%
“…We suggest these spatial disparities may reflect the probable role of NHERF1 not only in anchoring GLAST but probably in also complexing with other proteins that have PDZ binding motifs, such additional interactions precluding total colocalization at the molecular level and thus at the anatomic level. In light of the recent report that astrocytes in mouse brain show more restricted distribution of NHERF2 (Paquet et al, 2006), it is interesting to note that we find GLAST also binds NHERF2 in vitro (unpublished data); however, GLAST does not bind NHERF2 in vivo (as demonstrated by coimmunoprecipitation experiments).…”
Section: Nherf1 and Glast Interactionssupporting
confidence: 62%
See 1 more Smart Citation
“…Brain sections were then prepared and processed for pre-embedding immunoperoxidase labeling as previously described (18). Briefly, 60-m thick sections were incubated with rabbit anti-mGluR5 (1:2,000) or rabbit anti-NHERF-2 (1:7,000) followed by biotinylated anti-rabbit (1:200, Vector Laboratories Burlingame, CA), rinsed and then incubated with avidin-biotin-peroxidase complex (1:200, Vector Laboratories).…”
Section: Immunocytochemistry and Microscopymentioning
confidence: 99%
“…Our demonstration of rapid agonist-induced translocation of PMCA in a native cell type reveals a new mechanism for regulating Ca 2ϩ efflux. The recent identification of NHERFs in the brain and other excitable cells (66), and the fact that the brain specific PMCA 2b also binds NHERF-2 opens up the possibility that such mechanisms of regulation may be more widely operative.…”
Section: Discussionmentioning
confidence: 99%